2017
DOI: 10.1007/s11064-017-2191-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Complex I Activity is Conditioned by Supercomplex I–III2–IV Assembly in Brain Cells: Relevance for Parkinson’s Disease

Abstract: The assembly of complex I (CI) with complexes III (CIII) and IV (CIV) of the mitochondrial respiratory chain (MRC) to configure I-III- or I-III-IV-containing supercomplexes (SCs) regulates mitochondrial energy efficiency and reactive oxygen species (mROS) production. However, whether the occurrence of SCs impacts on CI specific activity remains unknown to our knowledge. To investigate this issue, here we determined CI activity in primary neurons and astrocytes, cultured under identical antioxidants-free medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…After pre-incubation for 3 min at 25°C, the reaction was initiated by the addition of NADH (100 μM, final concentration), and the rate of decrease in the absorbance was monitored at 340 nm for 1.5 min. The incubation in the presence of 1 μM rotenone completely abolished the NADH oxidase activity measured with this method, verifying that this activity corresponds to complex I [ 50 52 ]. The activity of the complex I was expressed as nmol of NADH oxidized/min/mgprot.…”
Section: Methodsmentioning
confidence: 59%
“…After pre-incubation for 3 min at 25°C, the reaction was initiated by the addition of NADH (100 μM, final concentration), and the rate of decrease in the absorbance was monitored at 340 nm for 1.5 min. The incubation in the presence of 1 μM rotenone completely abolished the NADH oxidase activity measured with this method, verifying that this activity corresponds to complex I [ 50 52 ]. The activity of the complex I was expressed as nmol of NADH oxidized/min/mgprot.…”
Section: Methodsmentioning
confidence: 59%
“…Together, these represent the functional entity for oxidative phosphorylation, and are linked together as one very large entity called the respirasome. Measurements in nematodes and mammals have shown that the enzymatic activity of complex I (transfer of electrons through the complex) is significantly higher when it is part of the entire supercomplex than when it is isolated further (Schafer et al 2006;Suthammarak et al 2009;Lopez-Fabuel et al 2017). In nematodes, unlike mice, for example, very little complex I exists in isolation; the majority of complex I that separates on digitonin containing BNGs exists as a supercomplex: either I:III 2 : IV n or I:III 2 (Suthammarak et al 2009).…”
Section: Mrcsmentioning
confidence: 99%
“…Humans, but not C57Bl/6 mice, express active Scaf1, a CIII-CIV assembly factor (Lapuente-Brun et al 2013). Recently, we have shown that the ability of mitochondria to assemble I-III 2 -IV SCs impacts on CI activity (Lopez-Fabuel et al 2017).…”
Section: Discussionmentioning
confidence: 98%